203 Infectious-like presentation of neuromyelitis optica with pyrexia and CSF lymphocytosis. Issue 12 (14th November 2019) - Cheema, Sanjay; Leddy, Sara; Wickremaratchi, Mirdhu
Abstract : A 19-year-old Philippine lady presented with persistent pyrexia over 39°C, abdominal pain and back pain. Over three days she then developed paraesthesia in all four limbs, proximal weakness in both legs, and sphincter disturbance. Vision was normal. Spinal cord MRI showed signal change and oedema from C2 to T12. CSF showed a lymphocytosis of 200 cells/mm 3 and protein of 1.0 g/L, with normal glucose. She was persistently febrile and was investigated extensively for an infectious myelitis and empirically treated with acyclovir and ceftriaxone. She made some improvement over the next two weeks and CSF lymphocyte count fell to 25 cells/mm 3 . T-SPOT was positive indicating latent Tuberculosis. CT body imaging was normal. Aquaporin-4 antibodies were positive. She was treated with high dose steroids, and mycophenolate was started after 3 months of anti-tuberculous medications. She went on to make a full neurological recovery. The persistent pyrexia was likely centrally generated due to high aquaporin-4 expression in the hypothalamus. This and the significant CSF lymphocytosis mimicked an infectious presentation and led to a late diagnosis and treatment with immunosuppression.